The Session Initiation Protocol Internet-centric signaling. - Schulzrinne, H.
The Session Initiation Protocol (SIP) provides advanced signaling and control functionality for a wide variety of multimedia services. SIP can efficiently and scalably locate resources based on a location-independent name and then negotiate session characteristics. It can find use in applications ranging from Internet telephony and conferencing to instant messaging, event notification, and the control of networked devices. We summarize the main protocol features and describe a range of extensions currently being discussed within the Internet Engineering Task Force
Keywords: Internet Engineering Task Force; Internet telephony; Internet-centric signaling; Session Initiation Protocol; Advanced signaling; Applications; Conferencing; Control functionality; Event notification; Instant messaging; Location-independent name; Multimedia services; Networked devices control; Resources location; Session characteristics